Association between C677T and A1298C MTHFR gene polymorphism and nonsyndromic orofacial clefts in the Turkish population: a case-parent study - (:unkn) unknown (TURKISH J PEDIATRICS, 2012)
Two common MTHFR gene polymorphisms (C677T and A1298C) have been implicated in the etiology of nonsyndromic cleft lip/palate (nsCL/P). To investigate the genotype association among nsCL/P in the Turkish population, 56 case-parent trios were recruited into the study. Genotype frequencies were compared to two groups of controls from the same population. A total of 46 case-parent trios were included in transmission disequilibrium test (TDT) analysis. The mothers of the study group had a higher frequency of 677TT genotype, with a three-fold increased risk of having nsCL/P offspring (odds ratio [OR]: 3.14, p=0.03). The combined 677CT/1298AC genotype was also common among these mothers (28%), but it did not reach statistical significance (OR: 2.27, p=0.07). TDT analysis for (C677T) T allele transmission did not reveal a significant association. In conclusion, mothers carrying 677TT genotype or with 677CT/1298AC combined genotype have increased risk of having nsCL/P offspring; therefore, higher periconceptional folic acid supplementation should be advised for decreasing the recurrence risk.
Keywords: nonsyndromic cleft lip palate; MTHFR polymorphisms; transmission disequilibrium test; METHYLENETETRAHYDROFOLATE REDUCTASE GENE; MATERNAL FOLATE INTAKE; RISK-FACTOR; LIP; HOMOCYSTEINE; GENOTYPE; PALATE; MUTATION; VARIANT